Impact of naval sonar signals on Atlantic herring (Clupea harengus) during summer feeding: - Sivle, L.D.; Kvadsheim, P.H.; Ainslie, M.A.; Solow, A.; Handegard, N.O.; Miller, P.J.O.; Nordlund, N.; Lam, F.P.A. (2012)
Naval anti-submarine sonars produce intense sounds within the hearing range of Atlantic herring (Clupea harengus). In this study, schools of Atlantic herring were exposed to sonar signals of 1–2 kHz (low-frequency active sonar, LFAS) and 6–7 kHz (mid-frequency active sonar, MFAS) and playbacks of killer whale feeding sounds during their summer feeding migration in the Norwegian Sea. The fish schools neither significantly dived nor changed their packing density in response to the LFAS and MFAS transmissions received by the fish at estimated sound pressure levels (SPLs; RMS) up to 176 and 157 dB re 1 mPa and estimated cumulative sound exposure levels up to 181 and 162 dB re 1 mPa2 s, respectively. In contrast, killer whale feeding sounds induced diving responses at received SPLs at -150 dB re 1 mPa. Herring behaviour was studied by using a 116-kHz hull mounted fishery sonar. This seems a promising method for studying the behaviour of free-ranging fish in situations in which other methods are difficult to use, such as migrating schools and fish close to the surface.